Light‐Activated Rhenium Complexes with Dual Mode of Action against Bacteria. Issue 13 (30th January 2020) - Frei, Angelo; Amado, Maite; Cooper, Matthew A.; Blaskovich, Mark A. T.
Abstract: New antibiotics and innovative approaches to kill drug‐resistant bacteria are urgently needed. Metal complexes offer access to alternative modes of action but have only sparingly been investigated in antibacterial drug discovery. We have developed a light‐activated rhenium complex with activity against drug‐resistant S. aureus and E. coli . The activity profile against mutant strains combined with assessments of cellular uptake and synergy suggest two distinct modes of action. Abstract : Shining a light on rhenium : A light‐activated rhenium complex with activity against drug‐resistant bacteria has been developed. The activity profile against mutant strains combined with assessments of cellular uptake and synergy suggest two distinct modes of action.